Baseline total lung capacity and all-cause mortality in restrictive pulmonary disorders: a meta-analysis - Fei Li; Yifan Chen; Guozhou Zhang; Mengyuan Liu; Huihui Zeng; Huaping Dai (BMC Pulmonary Medicine)
Abstract Rationale Forced vital capacity (FVC) has been utilized as a surrogate for vital capacity (VC) in monitoring the progression of restrictive pulmonary disorders, particularly in clinical trials of idiopathic pulmonary fibrosis (IPF). A dose-response relationship between decreased FVC and mortality in IPF has also been established. Since 2005, total lung capacity (TLC) has been routinely required to differentiate and diagnose restrictive pulmonary disorders. However, the relationship between changes in TLC change and the risk of mortality remains unclear. Objectives To investigate and quantify the relationship between changes in TLC and the risk of mortality in patients with restrictive pulmonary disorders. Methods This study employed a systematic review and meta-analysis following the PRISMA 2020 guidelines. Results A total of 26 studies were included in the meta-analysis, comprising a combined sample of 16,579 subjects, which included 7,961 females, 4,460 subjects in the relative low TLC group, and 12,119 subjects in the high TLC group. A reduced TLC was associated with an increased risk of all-cause mortality, as indicated by both unadjusted and adjusted hazard ratios. The unadjusted hazard ratio (95% CI) was 1.76 (1.32, 2.35), while the adjusted hazard ratio (95% CI) was 1.70 (1.31, 2.20). The risk ratio (RR) estimated from the studies that reported both the number of participants and deaths was RR (95% CI) = 2.01 (1.56, 2.60). The included studies demonstrated significant heterogeneity. Conclusion A low TLC at baseline, in comparison to individuals with relatively higher TLC, may increase the risk of all-cause mortality by at least 42–70% in cases of restrictive pulmonary disorders, although this conclusion is primarily based on observational studies, which carry low to moderate certainty.